Analisis Pendidikan Nilai Islam Di Era Industri 4.0 - luluk Indarinul Mufidah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2018)
Industrial Era 4.0 as a consequence of the development of human civilization which was marked by the development of the Internet of / for Things, whose presence was so fast. Which brings a lot of impact on social life, including the interaction patterns of today's young generation. Their lives are increasingly visible and appear to be realistic, individualistic, secularistic which is manifested in the form of disrespect, lack of sympathy, lack of empathy, the nature of help, mutual cooperation and even religion are considered to be mere places of emotion. Islamic religious education has a strategic meaning in Islamic education in particular and education in general. In the context of the religious structure of Indonesian society, Islamic education has an important role in the formation of national character and character.